A comparison of indices of respiratory failure in ventilated preterm infants. Issue 2 (1st September 2000) - Subhedar, N V; Tan, A T; Sweeney, E M; Shaw, N J
Abstract : AIM: To compare indices of respiratory failure in terms of their ability to predict adverse respiratory outcomes in preterm infants. The indices evaluated were: ( a ) the alveolar-arterial oxygen tension difference (A-aDo 2 ); ( b ) the ratio of arterial to alveolar oxygen tension (a/A ratio); ( c ) the oxygenation index (OI); ( d ) the fractional inspired oxygen concentration (Fio 2 ). METHODS: Details of respiratory support and arterial blood gas data in the first 24 hours of life were collected in ventilated infants below 34 weeks gestation. The worst single value of a particular index in the first 24 hours was chosen to quantify the severity of respiratory failure in each infant. Receiver operating characteristic curves were constructed and areas under the curve (AUC) calculated to compare the performance of the indices in predicting death from respiratory failure and/or the development of chronic lung disease (CLD). RESULTS: A total of 155 preterm infants were studied, of whom 35 (23%) died primarily from respiratory failure and 53 of the 120 survivors (44%) developed CLD. The overall performance of the four indices in predicting death from respiratory failure ranged from 0.77 (AUC for maximum Fio 2 ) to 0.88 (AUC for minimum a/A ratio). The corresponding AUCs for gestational age and birth weight were 0.75 and 0.76 respectively. In contrast, demographic variables tended to perform better than indices of respiratory failure in predicting CLD/death. CONCLUSIONS: There was no evidence of a significant difference between the performance of the a/A ratio, A-aDo 2, and OI in predicting adverse respiratory outcomes. Use of the OI is recommended because of its ease of calculation.